Evaluation of an Active Surveillance System for Stillbirths in Metropolitan Atlanta - Azofeifa, Alejandro (J Registry Manag, 2012)
BACKGROUND: In 2005, a pilot project was started at the Centers for Disease Control and Prevention (CDC) to expand an existing birth defects surveillance program, the Metropolitan Atlanta Congenital Defects Program (MACDP), to conduct active surveillance of stillbirth. This pilot project was evaluated using CDC’s current guidelines for evaluating surveillance systems. METHODS: We conducted stakeholder interviews with the staff of MACDP’s stillbirth surveillance system. We reviewed the published literature on stillbirth ascertainment including 4 previous publications about the MACDP stillbirth surveillance system. Using fetal death certificates (FDC) as a second, independent data source, we estimated the total number and prevalence of stillbirths in metropolitan Atlanta using capture-recapture methods, and calculated the sensitivity of the MACDP stillbirth surveillance system. RESULTS: The MACDP stillbirth surveillance system is useful, flexible, acceptable, and stable. The system’s data quality is improved because it uses multiple sources for case ascertainment. Based on 2006 data, estimated sensitivities of FDCs, MACDP, and both sources combined for identifying a stillbirth were 78.5%, 76.8%, and 95.0%, respectively. The prevalence of stillbirths per 1,000 live births and stillbirths was 8.2 (95% confidence interval [CI]: 7.5-9.0) based on FDC data alone and 9.9 (95% CI: 9.1-10.8) when combined with MACDP data. CONCLUSION: Use of MACDP as an additional data source for stillbirth surveillance resulted in higher levels of case ascertainment, better data quality, and a higher estimate of stillbirth prevalence than using FDC data alone. MACDP could be considered as a model to enhance stillbirth surveillance by other active birth defects surveillance programs.